El cuento como estrategia para mejorar la comunicación oral en el nivel inicial - García Tineo, Verónica Ysabel (2021)
The present work of professional sufficiency entitled "Storytelling as a strategy for the development of oral communication in the elementary level", corresponds to the area of communication and was developed with 4-year-old children. I consider this as a subject of great importance because every day there are difficulties in the oral expression of children; this affects other areas of development in their lives. Oral communication allows children better interaction and integration with family, society, and culture. The purpose of this capacity is to develop the ability to orally communicate their ideas and feelings freely. The work is based on the design of the learning activity with the competence: they communicate orally in their mother tongue, and the performance: participate in conversations, dialogues or listen to stories; with this, it was possible for the children to show their interest in communicative situations, describing a story with images and expressing their ideas or emotions. This work considers three important aspects: In the introductory part, the object of study, the purposes, the justification and importance of the work in the training of children are described. In the theoretical support, a reflection of the conceptual fundamentals of the area of communication and the importance it has in the way of expressing oneself, of communicating verbally is presented. The pedagogical support describes the pedagogical and didactic processes that are developed in a general way for the learning of children, considering that any process must achieve the integral formation of the students. These learning strategies were according to the interests and needs of 4 year old children of elementary education. The conclusions that have been reached after carrying out the present investigation are considered in the theoretical and practical aspect.